61 hours [compact disc, unabridged] : a Reacher novel - Child, Lee (Child, Lee. Jack Reacher novel, 2010)
When she discovers that a vicious assassin has his sights set on her, a woman preparing to testify against sinister forces in Bolton, South Dakota calls on the help of Jack Reacher, a former United States Army Military Police Major, whose tour bus recently crashed near the woman's town. Over the course of the next 61 hours, both their lives change dramatically in this climactic thriller.